PEMIKIRAN HARUN NASUTION TENTANG IJTIHAD DAN PERKEMBANGAN HUKUM ISLAM - Beni Firdaus (Alhurriyah, 2010)
Even though, Harun Nasution is not known as an expert of Islamic law, but he has some ideas about Islamic law, for instance, his idea concept about ijtihad and Islamic development. This article is mainly going to discuss about the main ideas of Harun Nasution. It is about the both ideas of Harun Nasution, either ijtihad or Islamic development. From the result of a study conducted stated that according to Harun Nasution, ijtihad is the third source of Islamic law after Al-Qur’an and As-sunah. Ijtihad is not limited to the field of law only. However, an idea about Islamic law is going to change suitable with the world development.